2022
DOI: 10.1007/978-981-19-1040-1_20
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging Wine Storytelling in the Tourist Experience: A Preliminary Study

Abstract: Wine tourism has long since ceased to be just a visit to wine producing regions and wineries, just to taste or buy wine. In fact, wine tourism has become more complex as a tourist product, due to the requirement of visitors to obtain a differentiated experience, composed of multiple elements Wine tourism activities consist of, above all, wine tastings and cellar, wine house and wine museum visits. Currently, and in the future, wine tourism has provided and boosted the creation of genuine and unique tourist exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…For instance, a qualitative study carried out in Greece analyzed verbal and visual representations and identified storytelling as effective for wine tourism (Bonarau et al , 2019). Considering that wine tourism has become a complex tourism product, this technique requires an authentic and emotional narrative to capture the tourist's attention and senses (Santos et al , 2022). According to this study by Santos et al (2022), storytelling can be seen as an antecedent of the wine experience, as this is invariably related to the winescape and an important influence of wine tourist behavior and makes the experience memorable (Ramšak, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a qualitative study carried out in Greece analyzed verbal and visual representations and identified storytelling as effective for wine tourism (Bonarau et al , 2019). Considering that wine tourism has become a complex tourism product, this technique requires an authentic and emotional narrative to capture the tourist's attention and senses (Santos et al , 2022). According to this study by Santos et al (2022), storytelling can be seen as an antecedent of the wine experience, as this is invariably related to the winescape and an important influence of wine tourist behavior and makes the experience memorable (Ramšak, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that wine tourism has become a complex tourism product, this technique requires an authentic and emotional narrative to capture the tourist's attention and senses (Santos et al , 2022). According to this study by Santos et al (2022), storytelling can be seen as an antecedent of the wine experience, as this is invariably related to the winescape and an important influence of wine tourist behavior and makes the experience memorable (Ramšak, 2022). Moreover, this technique can be a driver of the emotions of the wine tourist as well as a way of promoting the uniqueness of the wine region.…”
Section: Discussionmentioning
confidence: 99%
“…Además, ha convertido debilidades, como ser una pequeña área de producción en comparación con otras zonas vinícolas y su limitación orográfica, en fortalezas, poniendo en valor su terruño. También, ha sabido potenciar algunas de sus muchas fortalezas como son las variedades autóctonas o los sistemas de conducción de cultivos y ha puesto en valor los métodos de producción tradicionales o incluso recuperando en algunos parajes técnicas tradicionales de labrado que provienen de época romana, ya que, junto con el Priorato, son de las pocas comarcas vitivinícolas que utilizan caballerías para las labores de campo, lo que resulta atractivo para los nuevos consumidores que necesitan de historias en torno al vino como reclamo enoturístico (Elías Pastor, 2016;Santos et al, 2022). Asimismo, en el Bierzo existe una potencialidad en su territorio que puede ser aprovechada para generar oportunidades de mercado al incorporar a sus vinos elementos intangibles como son el valor de la historia, la cultura, etc., además de integrar, a través de la zonificación, aquellos elementos de trazabilidad en sus vinos que permitan conocer al cliente con certeza de qué localidad, paraje o incluso parcela viene el vino que está consumiendo.…”
Section: Conclusionesunclassified